(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
Geological investigations were carried out in the Sinawin-Sha’wa area, in northwestern Libya, in order to find suitable rocks for aggregate in asphalt mixtures for Nalut - Ghadamis Road reconstruction. By combined field work and micropetrographical analysis four different carbonate lithofacies were determined within Upper Cretaceous sedimentary sequence: lithofacies A - micritic limestones; lithofacies B - dolomitic marls; lithofacies C - dolobiomicrites; lithofacies D -biosparites and biosparudites. Diagenetic processes of cementation, recrystallization, dolomitization and silicification were identified within these lithofacies. Stone samples, taken from three lithofacies A, C, and D, were analyzed in order to determine its physical and mechanical properties (apparent density, open porosity, water absorption, uniaxial compressive strength). In addition, aggregate produced by crushing of the rock from lithofacies D is tested on resistance to crushing and abrasion (LA test). Samples from lithofacies B were not included in the testing of physical and mechanical properties since it is estimated as not suitable rock material for crushed aggregate. Samples from lithofacies A, C and D showed significant differences in the physical and mechanical properties. These differences stem from differences in mineralogical and petrographical composition as well as from diagenetic processes. Stone of lithofacies D were estimated as the most appropriate rocks available in the area, for aggregate in asphalt mixtures.